Social theory of learning in training of mathematics teachers - Riscanevo-Espitia, Lida Esperanza (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper reviews social theory of learning as a lens to ask mathematics teachers training. This conceptual referent assumes the concept of “practice community” as an analytical category to describe learning, highlighting its importance and analytical power, since the learning components -meaning, practice, community, and identity- can be integrated in it. This review presents a state of the art of different researches, which through the analysis of these components, allows considering the possibilities to highlight the who, the where, and the how the teacher takes part and collaborate in teachers training. In other words, it emphasizes on how the participants of these communities are considered the main actors in their training and professional culture. Finally, the challenge to conform practice communities as learning opportunities is recognized in the research outcomes.